MOLECULAR DOCKING, SINTESIS DAN UJI AKTIVITAS SITOTOKSIK SENYAWA 1-(3-KLOROBENZOIL)-1,3- DIMETILUREA - Dian Agung Pangaribowo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2013)
A novel 1-(3-chlorobenzoyl)-1,3-dimethylurea has been designed, synthesized, structurally determined, and the in vitro cytotoxic activity was evaluated. Docking simulation was performed to position this compound into the Checkpoint kinase 1 (Chk1) active site to determine the probable binding model. Synthesis of 1-(3-chlorobenzoyl)- 1,3-dimethylurea was completed by acylation reaction between 1,3-dimethylurea and 3-chlorobenzoyl chloride. The purity of synthesized product was determined by Thin Layer Chromatography and melting point measurement. Structure identification was performed by UV spectrophotometer, FT-IR and NMR spectrometer. Antiproliferative assay result demonstrated that this compound possessed good cytotoxic activity against HeLa cells, which is comparable to the positive control. This compound with potent cytotoxic activity might be a potential anticancer agent.